Hardware-in-the-Loop Testing of an Intelligent Electronic Device for Innovative UFLS Protection - Ilievska, R.; Mihalic, R.; Kushnikov, E.; Zakonjsek, J.; Rudez, U. (2021 IEEE Madrid PowerTech, 2021)
In recent years, electric power systems are subject to drastic changes. This affects the frequency stability due to the decreasing trend of the system inertia. To ensure stable system operation in the future, it is of great importance to make existing/conventional under-frequency load shedding protection schemes more adaptable and situation-aware under various volatile conditions. This paper presents the results of hardware-in-the-loop testing of an intelligent electronic device equipped with innovative load shedding algorithm. The results obtained from applying real-time digital simulations demonstrate that the innovation is robust, efficient and offers a very useful way of utilizing rate-of-change-of-frequency for under-frequency load shedding purposes.